An Over view on intuitionistic fuzzy topological spaces - M Abdy; Suzelawati Zenian; Irwan (IOP Publishing Ltd, 2021)
We present a brief overview some fundamental results on the intuitionistic fuzzy topological spaces, and give some introductory results about fuzzy open set, fuzzy closed set, fuzzy neighborhood, fuzzy interior set, fuzzy continuity, fuzzy compactness and fuzzy connectedness in these spaces.